(untitled) (Journal of Health Sciences, 2014)
Introduction: The lymphatic vasculature is an important route for the metastatic spread of human cancer. However, the extent to which this depends on lymphangiogenesis or on invasion of existing lymph vessels remains controversial. The goal of this study was to investigate the existence of lymphangiogenesis in invasive breast carcinoma: by measuring the lymphatic vessels density (LVD) and lymphatic endothelial cell proliferation (LECP) and their correlation with various prognostic parameters in breast cancer, including lymphovascular invasion (LVI).Methods: Lymphatic vessels density was investigated in 75 specimens of invasive breast carcinoma by immunostaining for D2-40 using the Chalkley counting method. Endothelial proliferation in lymphatic vessels was analyzed by dual-color immunohistochemistry with D2-40 and Ki-67.Results: Decrease of intra and peritumoral LVD in invasive breast carcinoma compared to fibrocystic breast disease was detected (p=0.002). Lymphatic endothelial cell proliferation was significantly higher in invasive breast cancer (p=0.008) than in the fibrocystic breast disease. LECP showed a correlation with histological grade of the tumor (p=0.05). Involvement of axillary lymph nodes with metastatic tissue was in strong correlation only with existence of lymphatic vascular invasion (p=0.0001).Conclusion: These results suggest that development of breast cancer promotes proliferation of lymphatic endothelial cells whose level correlates with histological grade of tumor, but in a scope that is insufficient to follow growth of tumor tissue that invades them and destruct them. This might explain the decrease of lymphatic vessels density.